2007
DOI: 10.1007/s00586-007-0432-9
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal intraoperative monitoring (MIOM) during 409 lumbosacral surgical procedures in 409 patients

Abstract: A prospective study on 409 patients who received multimodel intraoperative monitoring (MIOM) during lumbosacral surgical procedures between March 2000 and December 2005 was carried out. The objective of this study was to determine the sensitivity and specificity of MIOM techniques used to monitor conus medullaris, cauda equina and nerve root function during lumbosacral decompression surgery. MIOM has increasingly become important to monitor ascending and descending pathways, giving immediate feedback informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 12 publications
2
32
0
2
Order By: Relevance
“…The high sensitivity and specificity of MIOM during the different surgical procedures as presented in this supplement [10][11][12][28][29][30][31] document its advantages. It has been clearly shown that MEP monitoring improves outcome after surgery for intramedullary spinal tumors [27].…”
Section: Indications For Multimodal Intraoperative Monitoringmentioning
confidence: 75%
“…The high sensitivity and specificity of MIOM during the different surgical procedures as presented in this supplement [10][11][12][28][29][30][31] document its advantages. It has been clearly shown that MEP monitoring improves outcome after surgery for intramedullary spinal tumors [27].…”
Section: Indications For Multimodal Intraoperative Monitoringmentioning
confidence: 75%
“…Surgery was performed under general anesthesia using a laminoplasty approach in the prone position with multimodal intraoperative monitoring, as previously described. 2,21 Patients were transferred to the ward 24 hours after surgery. Mobilization under physiotherapeutic observation started 1-2 days after surgery.…”
Section: Surgery and Intraoperative Multimodal Neuromonitoringmentioning
confidence: 99%
“…19 Multimodal ION has resulted in increases in the sensitivity and specificity for neurologic injury to nearly 100%. [19][20][21][22] Neurologic injury within 30 days from the date of index surgery occurred in 1.8 and 2.0% of patients that underwent scoliosis surgery with and without ION, respectively. These rates are within the range of 0.5 to 3% risk of neurological injury reported in the literature for deformity surgeries.…”
Section: Discussionmentioning
confidence: 99%